Nonlinear radiation processes in solids - Baktybekov, K.S. (Publishing House of the KarSU named after E.A. Buketov, 2018)
There are some features in the research of the mechanisms of radiation exposure to solids, that complicate the understanding and quantitative description of such processes. First, the system "substance + radiation exposure" is open. In an open system, deviations of thermodynamic parameters from their equilibrium values lead to processes of energy and matter transfer. Secondly, the processes that occur as a result of the interaction of materials with radiation exposure are nonlinear. Continuous exchange of matter and energy with the environment leads to the fact that the system realizes stable dynamic equilibrium states that are far from the state of thermodynamic equilibrium. This conditions characterized by the existence of a certain spatial or temporal ordering so-called dissipative structure.
Keywords: chaos and structures; fractal; modeling of radiation defects; thermoluminescence